Efektywne wykorzystanie marketingu szeptanego w promocji usług kosmetycznych - Rams, Barbara (My University, 2012)
Sposób zarządzania firmą i jej promocją staje się bardzo istotnym elementem oraz tworzy jej przewagę konkurencyjną na rynku w danej branży. Marketing szeptany to nowoczesna, a zarazem bardzo skuteczna forma promocji i doskonałe źródło informacji na temat opinii klientów odnośnie jakości danej usługi. Potencjalny klient ma coraz większą świadomość konsumencką i dlatego tradycyjny marketing staje się coraz bardziej zawodny. W dzisiejszych czasach ludzie są bardziej skłonni wierzyć pozytywnym opiniom swoich znajomych niż reklamom telewizyjnym czy prasowym. Badania do niniejszej pracy przeprowadzone zostały w Gabinecie Stylizacji Paznokci w Nowym Sączu. Zdecydowałam się na zastosowanie metody badawczej jaką jest ankieta, a narzędziem badawczym kwestionariusz ankietowy. Na podstawie wyników badań jakie uzyskałam mogę stwierdzić, iż gabinet cieszy się bardzo dobrą opinią wśród osób ankietowanych, a wysoka jakość świadczonych tam usług jest polecana innym.

Both strategic management and promotion play a crucial role in creating the company’s competitive advantage within a given industry. One of the most effective forms of promotion in today’s business world is word-of-mouth advertising, which is at the same time an excellent source of customers’ opinions regarding the quality of a particular service. Potential clients are becoming increasingly aware of consumer options available in the market and tend to trust the opinions of their friends, acquaintances, or relatives rather than television commercials or press advertisements. Indeed, conventional forms of marketing are becoming less and less effective. The research for this paper has been conducted among the clients of Nail Styling Salon (Gabinet Stylizacji Paznokci) in Nowy Sącz. The marketing research method used was a survey, and the research tool used was a questionnaire. The results have showed that the Salon prides itself on excellent customer service as perceived by its current clients, who voluntarily spread their positive recommendations regarding the services provided by the Salon, thus recruiting new customers out of pure belief that they will provide benefit to other individuals.
Applying word-of-mouth marketing in beauty services promotion
Keywords: marketing szeptany; efektywna kampania reklamowa; poczta pantoflowa; promocja usług; word-of-mouth marketing; effective advertising campaign; services promotion